Encouraging Digital Technology in Neuropsychology: The Theory of Visual Attention on Tablet Devices. (24th February 2021) - Wang, Tianlu; Thielen, Hella; De Preter, Erik; Vangkilde, Signe; Gillebert, Céline R
Abstract: Objective: Visual attention helps us to selectively process relevant information and is crucial in our everyday interactions with the environment. Not surprisingly, it is one of the cognitive domains that is most frequently affected by acquired brain injury. Reliable assessment of attention deficits is pivotal to neuropsychological examination and helps to optimize individual rehabilitation plans. Compared with conventional pen-and-paper tests, computerized tasks borrowed from the field of experimental psychology bring many benefits, but lab-based experimental setups cannot be easily incorporated in clinical practice. Light-weight and portable mobile tablet devices may facilitate the translation of computerized tasks to clinical settings. One such task is based on the Theory of Visual Attention (TVA), a mathematical model of visual attention. TVA-based paradigms have been widely used to investigate several aspects of visual attention in both fundamental and clinical research, and include measures for general processing capacity as well as stimulus-specific attentional parameters. Methods: This article discusses the benefits of TVA-based assessments compared with frequently used neuropsychological tests of visual attention, and examines the reliability of a tablet-based TVA-based assessment in 59 neurologically healthy participants. Results: Pearson's correlations indicate that the tablet-based TVA assessment and the conventional lab-based TVA assessment have a comparable parallel-form (range: .67–.93), test–retest (range: .61–.78), and internal reliability (range: .56–.97). Conclusion: Our results suggest that tablet-based TVA assessment may be a promising tool to acquire clinical measures of visual attention at low cost at the bedside of the patient.